The Effect of Taxes on Corporate Financing Decisions - Evidence from the German Interest Barrier - Alberternst, Stephan; Sureth-Sloane, Caren
The literature suggests that when taking tax effects into account, debt ought to be prefer-able to equity. Thus, with all else being equal, levered firms are expected to show higher firm values.However, there are no uniform predictions of the size of this tax benefit from interest deductibility nor on the effect of changes in interest deductibility. We believe that the German corporate tax re-form in 2008, which introduced an interest barrier, can serve as a promising “quasi-experiment” to investigate the effects from a reform of interest deductibility. A study of this reform on the basis of German financial statement data is of general interest because, first, similar interest barriers have been introduced in several countries and proposed by the OECD to fight BEPS. Second, the major characteristics of the German tax system can be regarded as representative for most European and major Asian countries. Third, single entity financial statements for German companies allows us to capture tax and capital structure details that have not been available in most prior studies. With significance at the 5% level, we find evidence that the companies that are affected by the interest barrier reduce their leverage by 4.7 percentage points more than companies that are not affected by the interest barrier. We are the first to employ a detailed matching approach to the underlying rich dataset, which enables us to overcome several limitations of previous studies. Our results imply that capital structure reactions most likely have been underestimated in previous studies.

Uncertainty in Weighting Formulary Apportionment Factors. How Does Weighting Uncertainty Impact After-Tax Income of Multinational Groups?, - Ortmann, Regina
Formulary apportionment is an intensively debated mechanism for allocating tax base within multinational groups. Systems under which the formula is identical in all jurisdictions and systems under which jurisdictions can determine the weights on the formula factors individually can be observed. The latter systems produce uncertainty about the overall tax-liable share of the future group tax base. Counter-intuitively, I identify scenarios under which increased uncertainty leads to higher expected future group income. My results provide helpful insights for firms and policy makers debating the specific design of a formulary apportionment system.

Entscheidungskalküle US-amerikanischer Unternehmen bei Tax Inversions. What Drives the Decision of U.S. Firms to Expatriate? - Oßwald, Benjamin; Sureth-Sloane, Caren (Steuer und Wirtschaft International)

Investment Effects of Wealth Taxes under Uncertainty and Irreversibility - Niemann, Rainer; Sureth-Sloane, Caren

Mehr Theorie wagen: Eine neue Ausbildung für die Praxis? - Sureth, Caren (WiSt - Wirtschaftswissenschaftliches Studium)

Does mandatory IFRS adoption facilitate debt financing? - Florou, Annita; Kosi, Urska (Review of Accounting Studies)
We examine whether the mandated introduction of International Financial Reporting Standards (IFRS) is associated with the propensity to access the public rather than private debt market and the cost of debt. We use a global sample of public bonds and private loans and find that mandatory IFRS adopters are more likely, post-IFRS, to issue bonds than to borrow privately. We also find that mandatory IFRS adopters pay lower bond yield spreads, but not lower loan spreads, after the mandate. These findings are consistent with debt providers responding positively to financial reporting of higher quality and comparability, but only when there is a greater reliance on publicly available financial statements than private communication. Lastly, we document that the observed debt market benefits are concentrated in countries with larger differences between domestic GAAP and IFRS and are present even for EU countries that did not experience concurrent financial reporting enforcement or other institutional reforms. Overall, our study documents positive economic consequences around the mandated IFRS adoption for corporate debt financing and, in particular, for bond financing.
Keywords: Accounting regulation; IFRS; Accounting quality; Public and private debt markets; Cost of debt

Vermögensteuer und ihre Implikationen für den Wirtschaftsstandort Deutschland - eine betriebswirtschaftliche Analyse - Hoppe, Thomas; Maiterth, Ralf; Sureth-Sloane, Caren
Die (Wieder-)Einführung einer Vermögensteuer ist in den vergangenen Jahren erneut in den Fokus der politischen Diskussion gerückt. Der vorliegende Beitrag vermittelt einen Eindruck von den Belastungswirkungen, die aus der Umsetzung von aktuell vorliegenden Besteuerungskonzepten resultieren würden. Auf der Basis von realen Jahresabschlussdaten wird eine mehrperiodige Veranlagungssimulation durchgeführt, die insbesondere ermöglicht, den zu erwartenden Eigenkapitalverzehr sowie den Anstieg der Steuerbelastung für die betrachtete Unternehmensgruppe zu quantifizieren. Von besonderem Interesse sind hierbei Unternehmen deren laufende Erträge nicht ausreichen, um die Belastungen durch die Vermögensteuer zu tragen und damit einem Substanzverzehr ausgesetzt sind. Es zeigt sich, dass etwa die Hälfte der Unternehmen im Untersuchungszeitraum von sechs Jahren in mindestens einem Jahr einen Substanzverzehr erfährt. Der Vermögensteuer kommt somit keinesfalls der vielfach postulierte Charakter einer eher mäßig belastenden und im Wesentlichen substanzverschonenden Steuer zu. Zusatzbelastungen von knapp 100 bis zu 300% der Ertragsteuerlast sind keine Seltenheit und veranschaulichen das Gefährdungspotenzial dieser Steuer für den Wirtschaftsstandort Deutschland.
Keywords: Steuerbelastung; Substanzbesteuerung; ungleiche Vermögensverteilung; Veranlagungssimulation; Vermögensteuer

Editorial: What Is and What Is Not a Substantial Contribution? - Albers, Sönke; Sureth-Sloane, Caren (Business Research)

Can the CCCTB Alleviate Tax Discrimination against Loss-Making European Multinational Groups? - Ortmann, Regina; Sureth-Sloane, Caren

Can Tax Rate Increases Foster Investment Under Entry and Exit Flexibility? - Insights from an Economic Experiment - Fahr, Rene; Janssen, Elmar A.; Sureth-Sloane, Caren

Do Investors Request Advance Tax Rulings to Alleviate Tax Risk (and do tax authorities provide them)? A Joint Taxpayers’ and Tax Authorities’ View on Investment Behavior - Diller, Markus; Kortebusch, Pia; Schneider, Georg; Sureth-Sloane, Caren

Thin Capitalization Rules and Entrepreneurial Capital Structure Decisions - Maßbaum, Alexandra; Sureth-Sloane, Caren (Business Research)

IFRS 7 Disclosures and Risk Perception of Financial Instruments - Bischof, Jannis; Ebert, Michael (Schmalenbach Business Review)

Does mandatory IFRS adoption facilitate debt financing? - Florou, Annita; Kosi, Urska

Cost of Debt for Private Firms Revisited: Voluntary Audits as a Reflection of Risk - Koren, Jernej; Kosi, Urska; Valentincic, Aljosa

Determinants of corporate participation in the IFRS 4 (insurance contracts) replacement process - Kosi, Urska; Reither, Antonia (Accounting in Europe)
This study examines the determinants of financial firms' lobbying behaviour in the replacement process of International Financial Reporting Standard 4 (IFRS 4) Insurance Contracts. Based on comment letters in response to International Accounting Standards Board's (IASB) Exposure Draft 2010/8, we investigate firms' lobbying decisions and their long-term lobbying intensity. Using an international sample of publicly listed financial firms, we show that insurance companies and financially constrained IFRS firms are more likely to lobby the IASB. We also examine the long-term lobbying activity in the IFRS 4 replacement process during the years 2007–2010. We find that insurance companies and firms with dispersed ownership lobby more. Our results are stronger for IFRS firms compared to US generally accepted accounting principles users. Overall, we document intense lobbying by financial firms and present results that are largely consistent with economic consequences of anticipated accounting changes being the main driver of firms' lobbying behaviour. These results are in line with prior findings for non-financial firms.
Keywords: standard setting; IASB; corporate lobbying; financial firms; IFRS 4

Does Financial Statement Audit Reduce the Cost of Debt of Private Firms? - Koren, Jernej; Kosi, Urska; Valentincic, Aljosa (SSRN Electronic Journal)
This study examines the effect of audit on private firms’ cost of debt. We use a sample of 1,949 small private firms operating in the period 2006-2010 with optional financial statement audit. High quality data allows us to construct a more precise interest rate measure than existing studies employ. After controlling for obvious sources of demand for voluntary audits (ownership complexity, subsidiary status, bank relations), we find a robust central result that voluntary audits increase rather than decrease the cost of debt financing, contrary to several existing studies. This finding indicates that voluntary audits are generally treated as “adopting a label” and penalised by creditors, regardless of the perceived auditor quality as a result of the lemon problem in the audit market. Even Big-4 audits increase the cost of debt, likely as a result due to the lemon problem in the audit market, although the increase is smaller than for non-Big-4 audits. The results are sensitive to the estimation method used (OLS, Heckman’s two-step, PSM) and (sub-)sample selection. We show that disregarding the underlying assumptions of these estimation methods may lead to incorrect inferences. Additional analyses show that audited firms’ reported earnings are less informative about future operating performance than earnings of their unaudited counterparts. Our results also indicate that results are sensitive to cost of debt definition and this might have affected the results reported in the existing literature.

Besteuerung und Rechtsformwahl - König, Rolf; Sureth-Sloane, Caren

Der Einfluss von Steuern auf Investitionsentscheidungen bei Unsicherheit - Sureth, Caren

Does Financial Statement Audit Reduce the Cost of Debt of Private Firms? - Kosi, Urska; Koren, Jerney; Valentincic, Aljosa
This study examines the effect of audit on private firms’ cost of debt. We use a sample of 1,949 small private firms operating in the period 2006-2010 with optional financial statement audit. High quality data allows us to construct a more precise interest rate measure than existing studies employ. After controlling for obvious sources of demand for voluntary audits (ownership complexity, subsidiary status, bank relations), we find a robust central result that voluntary audits increase rather than decrease the cost of debt financing, contrary to several existing studies. This finding indicates that voluntary audits are generally treated as “adopting a label” and penalised by creditors, regardless of the perceived auditor quality as a result of the lemon problem in the audit market. Even Big-4 audits increase the cost of debt, likely as a result due to the lemon problem in the audit market, although the increase is smaller than for non-Big-4 audits. The results are sensitive to the estimation method used (OLS, Heckman’s two-step, PSM) and (sub-)sample selection. We show that disregarding the underlying assumptions of these estimation methods may lead to incorrect inferences. Additional analyses show that audited firms’ reported earnings are less informative about future operating performance than earnings of their unaudited counterparts. Our results also indicate that results are sensitive to cost of debt definition and this might have affected the results reported in the existing literature.
Keywords: private firms; voluntary audit; cost of debt; self-selection bias; lemon problem

Does Mandatory IFRS Adoption Improve the Credit Relevance of Accounting Information? - Kosi, Urska; Florou, Annita; Pope, Peter F.

Write-offs and profitability in private firms: Disentangling the impact of tax-minimisation incentives - Kosi, Urska; Valentincic, Aljosa (European Accounting Review)
Private firms are likely to use the financial reporting process more for other objectives, such as tax savings, than for communicating performance. However, observing firms choosing accounting policies for tax-minimisation purposes is not straightforward due to (i) tax and non-tax costs of reporting lower income (ii) accounting policies that result in lower reported income and no tax savings but generate non-tax benefits (iii) preparers' multiple incentives and (iv) econometric issues. We observe a large sample of 20,505 private firms writing off assets in two separate regimes, one that generates tax savings and one that does not. Firms significantly decrease, but continue to use, write-offs after the adverse change in tax treatment of write-offs. The exogenous tax change should not affect other reporting incentives. This allows us to disentangle the tax-minimisation incentive from other (un-observable) incentives, including debt contracting, dividends and employee relations that contribute to the observed anomalous positive relationship between write-offs and profitability. We show that for private firms (i) obtaining tax savings is important overall (ii) non-tax costs and benefits are probably also important and (iii) earnings informativeness for future cash flows increases after the adverse tax legislation change.

Does mandatory IFRS adoption facilitate debt financing? - Florou, Annita; Kosi, Urska

Sooner or Later? – Paradoxical Investment Effects of Capital Gains Taxation under Simultaneous Investment and Abandonment Flexibility - Niemann, Rainer; Sureth-Sloane, Caren (European Accounting Review)

Advance Pricing Agreements (APAs) als Instrument zur Vermeidung von Verrechnungspreiskonflikten – eine kritische Betrachtung - Vollert, Pia; Eikel, Carolin; Sureth-Sloane, Caren (Steuer und Wirtschaft)

Mehr Theorie wagen. Betriebswirtschaftslehre nach Bologna oder Hochschulbildung im Wandel - Sloane, Peter F. E.; Sureth-Sloane, Caren (Wirtschaft und Beruf)

Unternehmensführung und interkulturelle Hochschulbildung. Unternehmensführung in Europa - Interkulturelle Fragen - Sureth-Sloane, Caren (Wirtschaft und Beruf)

Wertorientierte Vergütung des Aufsichtsrats - Auswirkungen auf den Unternehmenswert - Ebert, Michael; Zein, Nicole (Betriebswirtschaftliche Forschung und Praxis)

Der Einfluss der Zinsschranke auf unternehmerische Kapitalstrukturentscheidungen - Maßbaum, Alexandra; Klotzkowski, Tasja; Sureth-Sloane, Caren (Zeitschrift für Betriebswirtschaft)

Does insider shareholding matter to corporate payout reactions to tax reforms? - Sureth-Sloane, Caren (Zeitschrift für Betriebswirtschaft)

Die Einkommensbesteuerung von international tätigen Künstlern, Sportlern, Artisten und unterhaltend Darbietenden - Führt die Neuregelung zu einer gleichmäßigen Besteuerung? - Dahle, Claudia; Sureth-Sloane, Caren; Stamm, Katharina (Steuern und Bilanzen)

ProDok Helps to Transform Doctoral Training at Business Schools in German-Speaking Countries - Jahnke, Hermann; Sureth-Sloane, Caren (POMS Chronicle)

The Mixed Accounting Model Under IAS 39: Current Impact on Bank Balance Sheets and Future Developments - Ebert, Michael; Bischof, Jannis (The Capco Institute Journal of Financial Transformation)

The Impact of Differential Capital Income Taxation on the Value of Risky Projects - Niemann, Rainer; Sureth-Sloane, Caren (Economics Bulletin)

§§ 20 bis 23 UmwStG: Die Einbringung von Unternehmensteilen in eine Kapitalgesellschaft - Ansatz von Buchwerten oder gemeinen Werten - Maßbaum, Alexandra; Sureth-Sloane, Caren (Steuer und Studium)

Handels- und steuerrechtliche Kapitalkontenfortschreibung und deren Einfluss auf die Verlustverrechnung bei Personengesellschaften - Kopplin, Anja; Maßbaum, Alexandra; Sureth-Sloane, Caren (Die Wirtschaftsprüfung)

Empirische Analyse der Unternehmensbewertung für die Erbschaftsteuer mit dem vereinfachten Ertragswertverfahren - Müller, Jens; Sureth-Sloane, Caren

Mögliche Fallstricke einer Optimierung unternehmerischer Investitionsentscheidungen auf der Grundlage der Konzernsteuerquote - Müller, Jens; Sureth-Sloane, Caren; Läufer, Christian (Die Wirtschaftsprüfung)

Wichtigste Einflussfaktoren auf die steuerliche Verlustnutzung bei Personengesellschaften - Sureth-Sloane, Caren (Steuer und Studium)

Besteuerung multinationaler Unternehmen in der EU – eine vergleichende Analyse ausgewählter Reformvorschläge - Sureth-Sloane, Caren; Bäumer, Michaela (Zeitschrift für Betriebswirtschaft)

Capitalized investments with entry and exit options and paradoxical tax effects - Schneider, Georg; Sureth-Sloane, Caren (Review of Managerial Science)

Wie attraktiv sind Beteiligungsinvestitionen nach der Begrenzung der Verlustnutzung bei Anteilskäufen durch § 8c KStG? - Sureth-Sloane, Caren; Vollert, Pia (Corporate Finance biz)

The Impact of Tax Optimized Investment Projects on the Effective Group Tax Rate - Müller, Jens; Sureth-Sloane, Caren (Die Betriebswirtschaft)

Grenzüberschreitende Verlustverrechnungssysteme in Europa – Vorbilder für eine Reform der deutschen Organschaft? - Sureth-Sloane, Caren; Mehrmann, Annika; Dahle, Claudia (Steuer und Wirtschaft)

Mikroanalytische Begleitung der Steuerpolitik am Beispiel der Erbschaftsteuerreform - Maiterth, Ralf; Houben, Henriette; Broekelschen, Wiebke; Müller, Jens; Sureth-Sloane, Caren (Statistik und Wissenschaft)
Erbschaftsteuer | Inheritance tax | Steuerreform | Tax reform | Steuerwirkung | Tax effects | Steuereinnahmen | Tax revenue | Mikrodaten | Microdata | Simulation | Deutschland | Germany
Keywords: Erbschaftsteuer | Inheritance tax | Steuerreform | Tax reform | Steuerwirkung | Tax effects | Steuereinnahmen | Tax revenue | Mikrodaten | Microdata | Simulation

Bilanzpolitisches Potential im Rahmen der Goodwillbilanzierung - Transaktionsgestaltung beim Unternehmenserwerb - Ebert, Michael; Simons, Dirk (KoR : Zeitschrift für internationale und kapitalmarktorientierte Rechnungslegung)

International corporate reporting: A comparative approach, by Clare Roberts, Pauline Weetman and Paul Gordon (fourth edition) - Kosi, Urska (The International Journal of Accounting)

Versinkt die Kapitalmarkttheorie in logischen Widersprüchen, oder: Ist arqus e.V. aus dem Schneider? - Blaufus, Kay; Hundsdoerfer, Jochen; Kiesewetter, Dirk; König, Rolf J.; Kruschwitz, Lutz; Löffler, Andreas; Maiterth, Ralf; Müller, Heiko; Niemann, Rainer; Schanz, Deborah; Sureth-Sloane, Caren; Treisch, Corinna (Schmalenbachs Zeitschrift für betriebswirtschaftliche Forschung)

arqus-Stellungnahme zur notwendigen Reform der Abgeltungssteuer - Kiesewetter, Dirk; Niemann, Rainer; Hundsdoerfer, Jochen; Knirsch, Deborah; König, Rolf; Kruschwitz, Lutz; Löffler, Andreas; Maiterth, Ralf; Müller, Heiko; Sureth-Sloane, Caren; Treisch, Corinna (Der Betrieb)

arqus-Stellungnahme: Das BilMoG - Eine Chance zur Steuervereinfachung? - Knirsch, Deborah; Müller, Heiko; Blaufus, Kay; Hundsdoerfer, Jochen; Kiesewetter, Dirk; König, Rolf; Kruschwitz, Lutz; Löffler, Andreas; Maiterth, Ralf; Müller, Heiko; Sureth-Sloane, Caren; Treisch, Corinna (Deutsches Steuerrecht)

Steuern und Risiko als substitutionale oder komplementäre Determinanten unternehmerischer Investitionspolitik? - Niemann, Rainer; Sureth-Sloane, Caren

Auswirkungen einer Reform des Erbschaft- und Schenkungsteuergesetzes auf das Steueraufkommen unter besonderer Berücksichtigung einer verkehrswertorientierten Bewertung von Unternehmens- und Grundvermögen - Sureth-Sloane, Caren; Müller, Jens; Houben, Henriette; Maiterth, Ralf (Untrnehmensbesteuerung 2008: Neue Wege gehen)

Asset Write-Offs in the Absence of Agency Problems - Garrod, Neil; Kosi, Urska; Valentincic, Aljosa (Journal of Business Finance and Accounting)
Using a large sample of small private companies, we show incremental influence ofeconomic incentives over prescriptions from accounting standards by financial statementpreparers in a code‐law setting with high alignment between financial and tax reportingand no agency problems. Contrary to predictions from standards, more profitable companiesare more likely to write‐off and the write‐off magnitude is greater, reflecting taxminimisation. Larger companies are more likely to write‐off, but the magnitude decreaseswith size, reflecting increasing political costs due to greater visibility to taxauthorities. Previous write‐off patterns and magnitudes are persistent, reflectinginstitutional learning linked to regulatory changes.

The impact of minimum taxation by an imputable wealth tax on capital budgeting and business strategy of German companies - Sureth-Sloane, Caren; Maiterth, Ralf (Review of Managerial Science)

Steuern und Risikobereitschaft in Modellen irreversibler Investitionen - Niemann, Rainer; Sureth-Sloane, Caren (Journal für Betriebswirtschaft)

arqus-Stellungnahme: Das BilMoG - Eine Chance zur Steuervereinfachung? - Müller, Heiko; Blaufus, Kay; Hundsdoerfer, Jochen; Kiesewetter, Dirk; König, Rolf; Kruschwitz, Lutz; Löffler, Andreas; Maiterth, Ralf; Niemann, Rainer; Sureth-Sloane, Caren; Treisch, Corinna (Deutsches Steuerrecht)

arqus-Stellungnahme zur faktischen Abschaffung der Erbschaftsteuer für Unternehmer - Maiterth, Ralf; Niemann, Rainer; Blaufus, Kay; Kiesewetter, Dirk; Knirsch, Deborah; König, Rolf; Hundsdoerfer, Jochen; Müller, Heiko; Sureth-Sloane, Caren; Treisch, Corinna (Der Betrieb)

Unternehmensfinanzierung, Unternehmensrechtsform und Besteuerung - Maiterth, Ralf; Sureth-Sloane, Caren

Steuerreformen und Übergangsprobleme bei Beteiligungsinvestitionen - Sureth-Sloane, Caren

Advances in performance measurement: evidence from Slovenian companies - Tekavic, Metka; Peljhan, Darja; Kosi, Urska (Accounting and Finance in Transition)

Advances in Performance Measurement: Evidence from Slovenian Companies - Peljhan, Darja; Tekavcic, Metka; Kosi, Urska (Accounting and Finance in Transition)
Performance measurement systems are the focus of considerable attention in academic and practitioner communities as they contribute to the management of organisational performance. The literature suggests that companies have to put much more emphasis on non-financial measures than they did in the past and that they should implement some kind of integrated performance measurement system. The purpose of our exploratory study was to find out characteristics of performance measurement and management in Slovenian companies. We conducted a survey ‘Performance management in Slovenian companies’ in the spring of 2003. Our sample consists of 108 Slovenian companies. The research results show that Slovenian companies still perceive financial performance measures as more important than non-financial, although they measure both perspectives of their business. Also, we found out that companies measure their performance unsystematically as only 54 per cent of companies that have not changed their performance measurement methods in the last five years use balanced scorecard or some other form of integrated performance measurement system.

Unternehmensfinanzierung, Unternehmensrechtsform und Besteuerung - Maiterth, Ralf; Sureth-Sloane, Caren (Betriebswirtschaftliche Forschung und Praxis)

Verbessern Tax-Master- und WP-Master-Studiengänge die Ausbildungsqualität von Steuerberatern und Wirtschaftsprüfern? - Bareis, Peter; Hachmeister, Dirk; Kahle, Holger; Kiesewetter, Dirk; König, Rolf; Maiterth, Ralf; Niemann, Rainer; Rückle, Dieter; Schneider, Dieter; Siegel, Theodor; Sureth-Sloane, Caren; Treisch, Corinna (Zeitschrift für Steuern und Recht)

Auswirkungen der Vermögensteuer als Mindeststeuer auf die Investitionstätigkeit und die Attraktivität Deutschlands im internationalen Standortwettbewerb - Maiterth, Ralf; Sureth-Sloane, Caren (Steuern und Bilanzen)

Wiedereinführung der Vermögensteuer als Mindeststeuer in Deutschland - Unlösbare Probleme bei der Bewertung von Grundbesitz und Unternehmen - Maiterth, Ralf; Sureth-Sloane, Caren (Steuern und Bilanzen)

Wealth Tax As Alternative Minimum Tax? - The Impact of a Wealth Tax on Business Structure and Strategy - Sureth-Sloane, Caren; Maiterth, Ralf

Capital Budgeting with Taxes under Uncertainty and Irreversibility - Niemann, Rainer; Sureth-Sloane, Caren (Journal of Economics and Statistics)

Aktuelle Änderungen beim Betriebsausgabenabzug - Geschenke, Bewirtungskosten, Fahrtkostenzuschüsse und Halbjahres-AfA - Sureth-Sloane, Caren; Müller, Jens; Nordhoff, Daniel (BBK - Buchführung, Bilanzierung, Kostenrechnung)

Modelle für die Vermögensbesteuerung von natürlichen Personen und Kapitalgesellschaften - Konzepte, Aufkommen, wirtschaftliche Wirkungen - Bach, Stefan; Haan, Peter; Maiterth, Ralf; Sureth-Sloane, Caren (DIW Berlin: Politikberatung kompakt)

Tax neutrality under irreversibility and risk aversion - Niemann, Rainer; Sureth-Sloane, Caren (Economics Letters)

Taxation under Uncertainty – Problems of Dynamic Programming and Contingent Claims Analysis in Real Option Theory - Niemann, Rainer; Sureth-Sloane, Caren

Partially Irreversible Investment Decisions and Taxation under Uncertainty: A Real Option Approach - Sureth-Sloane, Caren (German Economic Review)